2019
DOI: 10.1002/pola.29495
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymethacrylate‐bearing benzocyclobutene structure and extension to networked polymer based on thermal isomerization

Abstract: 1‐Benzocyclobutenyl methacrylate‐bearing methacrylate (BCBMA) backbone has been synthesized, and radical polymerization of the monomer was performed by utilizing 2, 2′‐azobisisobutyronitrile (AIBN) as initiator to result poly‐BCBMA. Differential scanning calorimetry (DSC) measurement of the derived poly‐BCBMA revealed the lowering of thermal isomerization temperature from that of nonsubstituted benzocyclobutene. The thermal decomposition temperature of BCBMA before and after thermal treatment was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The FTIR spectrum of 1 showed the characteristic absorption of thiocarbonyl group (CS) at 1186 cm −1 , whereas the absorption of CS was completely eliminated and the absorption due to carbonyl group (CO) appeared at 1637 cm −1 in the FTIR spectrum of 1b . This result indicated that the ring‐opening polymerization of 1 successfully proceeded and afforded 1b having the isomerized dithiocarbonate structure in the main chain 24 . On the other hand, the peak due to the CC absorption at 1628 cm −1 disappeared in the FTIR spectrum of 1a .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The FTIR spectrum of 1 showed the characteristic absorption of thiocarbonyl group (CS) at 1186 cm −1 , whereas the absorption of CS was completely eliminated and the absorption due to carbonyl group (CO) appeared at 1637 cm −1 in the FTIR spectrum of 1b . This result indicated that the ring‐opening polymerization of 1 successfully proceeded and afforded 1b having the isomerized dithiocarbonate structure in the main chain 24 . On the other hand, the peak due to the CC absorption at 1628 cm −1 disappeared in the FTIR spectrum of 1a .…”
Section: Resultsmentioning
confidence: 90%
“…This result indicated that the ring-opening polymerization of 1 successfully proceeded and afforded 1b having the isomerized dithiocarbonate structure in the main chain. 24 On the other hand, the peak due to the C C absorption at 1628 cm À1 disappeared in the FTIR spectrum of 1a. Additionally, the absorption of C S was observed at 1186 cm À1 in the FTIR spectrum of 1a, indicating the structure of 1a having a cyclic dithiocarbonate moiety in the side chain.…”
Section: Cationic Ring-opening Polymerization Of Monomermentioning
confidence: 95%
See 2 more Smart Citations